Cutaneous Neuroimmune Interactions in Peripheral Neuropathic Pain States - Lowy, Daniel B.; Makker, Preet G. S.; Moalem-Taylor, Gila (Frontiers in Immunology, 2021)
Bidirectional interplay between the peripheral immune and nervous systems plays a crucial role in maintaining homeostasis and responding to noxious stimuli. This crosstalk is facilitated by a variety of cytokines, inflammatory mediators and neuropeptides. Dysregulation of this delicate physiological balance is implicated in the pathological mechanisms of various skin disorders and peripheral neuropathies. The skin is a highly complex biological structure within which peripheral sensory nerve terminals and immune cells colocalise. Herein, we provide an overview of the sensory innervation of the skin and immune cells resident to the skin. We discuss modulation of cutaneous immune response by sensory neurons and their mediators (e.g., nociceptor-derived neuropeptides), and sensory neuron regulation by cutaneous immune cells (e.g., nociceptor sensitization by immune-derived mediators). In particular, we discuss recent findings concerning neuroimmune communication in skin infections, psoriasis, allergic contact dermatitis and atopic dermatitis. We then summarize evidence of neuroimmune mechanisms in the skin in the context of peripheral neuropathic pain states, including chemotherapy-induced peripheral neuropathy, diabetic polyneuropathy, post-herpetic neuralgia, HIV-induced neuropathy, as well as entrapment and traumatic neuropathies. Finally, we highlight the future promise of emerging therapies associated with skin neuroimmune crosstalk in neuropathic pain.